Evaluation of sustainability in university tutoring programs for educational leadership: a case study - Villarrubia Zúñiga, María Soledad; Ortiz-Jiménez, Macarena; González García, Paula; Suárez-Campos, Laura (Frontiers in Education, 2024)
University tutoring programs should aim to create a conducive environment for promoting pedagogical practices that align with the principles of Education for Sustainable Development (ESD). However, it has been observed that teachers often face difficulties when implementing ESD in tutoring sessions, such as lack of time, students' reluctance to share personal issues, and insufficient training and resources. This research is part of a larger project that aims to study university tutoring as a pedagogical tool to identify problems affecting students' learning processes and provide solutions to improve the quality of teaching. As participatory and dialogical models are most appropriate for promoting ESD, a well-developed tutoring model will contribute to the creation of useful pedagogical practices to guide and improve the status quo of students. Through an exploratory-descriptive study, this paper compares two university tutoring programs in Spain and Morocco to identify the most frequent issues hindering educational leadership and sustainable development, which can impact academic success. actions that can be implemented to achieve the fourth Sustainable Development Goal (SDG4) of the 2030 Agenda signed by all members of the United Nations in 2015.This study aims to analyze the most challenging issues encountered by students enrolled in the Early Childhood and Primary Education degrees at Alicante University in Spain and L2 students studying different degrees at the Euro-Mediterranean University of Fez in Morocco. Data collection is taken directly from the questions raised during university tutoring sessions in both universities. The main objective is to improve and provide a well-rounded and comprehensive support system to students. Drawing from tutors' experiences, this research examines the issues requiring more urgent attention and guidance to respond most effectively to students' needs. Ultimately, this case study will enable us to identify areas for improvement in the quality of learning.The theoretical underpinnings of this study rely on previous research about the importance of university tutoring and the need to approach this topic as a multidisciplinary and complex research area. Those works have identified and corroborated that tutoring at university has three key dimensions: 'personalsocial', 'academic' and 'professional' (